Monitoring the temperature and vibration response of underground optical fibres collocated with the EAC power distribution cables using state-of-the-art distributed sensing instruments - Ioannou, Andreas; Kouzoupou, Charalambos; Argyrou, Maria C.; Kalli, Kyriacos; Mondanos, Michael; Marchesini, Pierpaolo; Hunter, Ian; Karaulanov, Rumen; Stavrou, Andreas; Papaconstantinou, Marios (My University, 2022)
We present a study on the use of state-of-the-art distributed sensing systems to extract temperature and vibration information from existing single-mode, optical fibre infrastructure in Cyprus (~25-year-old installation); as a means of optical fibre distributed sensing. In this study, we have focused on the underground optical fibres of the Electricity Authority Cyprus (EAC). The optical fibres have been selected to be collocated with existing underground power distribution cables that are sited in and around Nicosia, for the purpose of monitoring power cable joints that are prone to failure, along with general monitoring for unusual behaviour and potential cable fault conditions. Three state-of-the-art distributed sensing systems have been deployed to run in parallel, on the same optical cable branch and all optimised for use with single-mode fibre. The underground power cables were monitored using a fast Brillouin optical time-domain reflectometer (BOTDR, with temperature and vibration measurement capability), a Distributed Temperature Sensor (Silixa, single-mode DTS) and an intelligent Distributed Acoustic Sensor (Silixa, iDAS). The results include calibration methods performed under controlled laboratory conditions for the fibres under test, prior to field deployment. The field data, recovers both temperature and vibration measurements over a 3-month period the results of which will be presented.
Keywords: temperature; vibration response; power distribution